Changing Epidemiology of Stroke in Nepalese Population - Thapa, Amit; KC, Bidur; Shakya, Bikram; Yadav, Dipesh Kumar; Lama, Karjome; Shrestha, Rabindra (Nepal Journal of Neuroscience, 2018)
Corrigendum: The article published in Nepal Journal of Neurosciences 2018;15:10-18 by Amit Thapa et al was mistakenly published with wrong affi liation of some of the co-authors. The correct affi liation of the co-authors should read as Bikram Shakya, MBBS, MS, MCh Lecturer Department of Neurological Surgery Kathmandu Medical College Teaching Hospital (KMCTH) Sinamangal, Kathmandu, Nepal Dipesh Kumar Yadav, MBBS Medical Officer Department of Neurological Surgery Kathmandu Medical College Teaching Hospital (KMCTH) Sinamangal, Kathmandu, Nepal Karjome Lama, MBBS Medical Officer Department of Neurological Surgery Kathmandu Medical College Teaching Hospital (KMCTH) Sinamangal, Kathmandu, Nepal Abstract: We are witnessing changing patterns in stroke in our practice. Documenting changes in epidemiological profile are important for public health policy. We hereby present analysis of patients with stroke to stress upon the dynamics and update the improvement in their care. We retrospectively studied all patients with first time stroke presenting in Kathmandu Medical College Teaching Hospital during June 2012 till November 2015. Diagnosis was made on clinico-radiological basis with prospective follow up for at least 1 year from the event. Risk factors as well outcome in terms of Glasgow outcome score were studied. Statistical analysis was performed on SPSS. A total of 1017 patients of 16260 patients admitted to the hospital during the study period had first time stroke, a hospital based annual incidence of stroke of 64 per thousand admissions was hence calculated. Mean age was 55 years with 60.5% males. 503 patients (49.5%) had infarction with 20 patients having hemorrhagic conversion while 3 had TIA. 50.2% had hemorrhagic stroke. 56.7% females had ischemic stroke whereas 54.9% of males had hemorrhagic stroke (p=0.002). Common risk factors like HTN (54.7%), Smoking (41.5%), Alcohol (39.2%), dyslipidemia (34.1%) and DM (4.8%) were seen with stroke however, active smoker were more at risk of hemorrhagic stroke (p=0.000) while diabetic patients for ischemic stroke (p=0.000). Due to availability of neurosurgical services, 14.6% patient could undergo procedures like decompressive craniectomy, hematoma evacuation, CSF diversion procedures and carotid endarterectomy for stroke. 66.9% patients required surgical intervention within 48 hours of admission. We had 30 days mortality of 0.5% mortality in this series (majority in hemorrhagic stroke), however over 3 years duration of study mortality rose to 8.3% (majority in ischemic stroke). Almost 88.5% patients achieved mRS< Nepal Journal of Neuroscience, Volume 15, Number 1, 2018 11 2 over a period of 3 years. Persistent vegetative state was seen in 7.6% cases after 1 year. We observe a very high incidence of hemorrhagic stroke in general with higher than reported proportion of females being involved with ischemic stroke in our series. Most of the vegetative state conditions occurred in ischemic stroke patients however early mortality was common in hemorrhagic stroke. This change in pattern of stroke as well as need of surgical intervention mandates early involvement of neurosurgical services. Poor long term prognosis in ischemic stroke may be reversed by timely thrombolytic services and prevented by mitigating risk factors. Nepal Journal of Neuroscience 15:10-18, 2018